The production of alkaloids in Annona cacans seedlings is affected by the application of GA4+7 + 6-Benzyladenine - Sousa, Marília Caixeta [UNESP]; Bronzatto, Andréia Cristina [UNESP]; González-Esquinca, Alma Rosa; Campos, Felipe Girotto [UNESP]; Dalanhol, Samanta Jaqueline; Boaro, Carmen Sílvia Fernandes [UNESP]; Martins, André Luis [UNESP]; da Silva Almeida, Jackson Roberto Guedes; Costa, Emmanoel Vilaça; De-la-Cruz-Chacón, Iván; Ferreira, Gisela [UNESP] (Elsevier, 2019)
The Annonaceae family presents alkaloids with ecological functions and pharmacological interest. This is the first study to evaluate if the application of plant growth regulators to seeds of this family alters the production of alkaloids over time from germination. This study was carried out in four sequential stages of Annona cacans Warm. development from the resumption of embryo during seed imbibition with the application of plant regulator GA4+7 + 6-Benzyladenine. The concentration of total alkaloids was quantified using the oxoaporphine alkaloid liriodenine as reference standard. In addition, the liriodenine concentration was measured and the profile evaluated by ultra-high-performance liquid chromatography (UHPLC). Results have shown that alkaloids are present in all phases and in all tissues, at higher concentrations in roots (up to 100 times). The proportion of total alkaloids and liriodenine was modified in response to the application of plant regulators. Roots doubled the content of alkaloids and liriodenine. In cotyledonary leaves, the amount of total alkaloids decreased; however, liriodenine remained unchanged. Our results have shown that the use of plant growth regulators based on gibberellins and cytokinins modified the production of alkaloids in tissues in a specific way.
Keywords: Annonaceae; Cytokinin; Gibberellin; Liriodenine; Plant hormones; Specialized metabolism